Renewable energy consumption in Sub-Saharan Africa: The role of human capital, foreign direct investment, financial development, and institutional quality - Ahmad Nawaz; Mohammad Mafizur Rahman (Energy Reports, 2023)
The Sub-Saharan Africa is facing trilemma of energy poverty, climate change hazards, and low economic growth. Lack of access to modern energy is considered as an impediment to the region’s wellbeing and development objectives. This study contributes to the energy literature by examining the role of financial development, institutional quality, foreign direct investment, and direct and indirect effects of human capital on the renewable energy consumption of 31 Sub-Saharan African countries over the period 2002–2019. Panel corrected standard error (PCSE) and feasible generalized least square (FGLS) estimation methods are applied for empirical investigation. The findings reveal that complementary effect of both human capital and GDP per capita is a key policy choice for the sample countries. The study also validates a U-shaped GDP-energy consumption nexus. Thus the present work provides a novel and insightful empirical evidence on energy transition and the channels through which it is affected by human capital, financial development, and institutional quality. Therefore, it is recommended that improvement in GDP per capita, capacity enhancement of human capital, and reforms in financial and institutional frameworks entail strategic importance for energy transition.